Interlanguage impoliteness in criticism by the English learners from Javanese background over social status and distance - Suwignyo, Eko; Rukmini, Dwi; Hartono, Rudi; Pratama, Hendi (Journal of Education and Learning (EduLearn), 2024)
The present study analyses the impoliteness of criticism over social status and distance, incorporating the concept of "levels of imposition." Criticism as a fundamental speech act is commonly used by people in the modern era, either in the digital world or the real world. It usually contains impoliteness if it embodies negative behavior, conveying criticism. This study belonged to an interlanguage pragmatics study and used forty participants from English language learners having Javanese backgrounds. It also applied the role play technique to take data to be analyzed using mixed method analysis. The data showed that the criticizer performed various impoliteness strategies in criticism, considering familiar and unfamiliar relationships in different social status levels. They mainly performed bald-on-record impoliteness and adhered to other strategies such as negative, positive, and mock politeness. Besides that, delivering criticism in high intonation was also perceived as a part of impoliteness. Therefore, it suggested conducting another research concerning paralinguistics and impoliteness in various communication contexts.